Efficiency of Genetic Transformation via Pollen-Tube Pathway of Jatropha (Jatropha curcas L.) Based on Histochemical and Molecular Analysis - Zainudin, Agus; Purwoko, Bambang Sapta; Santoso, Tri Joko; Ardie, Sintho Wahyuning; Trikoesoemaningtyas, and (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
The genetic transformation via pollen-tube pathway is an alternative method to overcome the constraints imposed by genotype specificity in transformation and regeneration in jatropha (Jatropha curcas L.) tissue culture. Therefore, it is necessary to establish important parameters for efficient genetic transformation of jatropha via pollen-tube pathway. The objective of the research was to study the efficiency of direct transformation of jatropha via pollen-tube pathway based on histochemical and molecular analysis. Solution of purified pCAMBIA1301 DNA plasmid carrying a hptII marker gene and a gus reporter gene with concentration level of 0.05, 0.25, 0.50 µg µl-1 were applied to stigma of flowers at 1, 2, 4, 7, 10 h after pollination. Seedling of IP3A, IP3P and JcUMM18 jatropha’s genotypes derived from 15 combination treatments of plasmid DNA concentration and application time, also wild type was subjected to histochemical and molecular analyses. Based on those analyses, the efficiency of transformation via pollen-tube pathway of three jatropha genotypes ranged from 1.5-16.7%. PCR analysis showed that a number of positive plants were identified by using specific primers hptII and gus, i.e. 1-3 and 3-7 plants of the 15 combined treatments, respectively. It indicated that the transformation efficiency via the pollen-tube pathway varied in each jatropha genotype.Keywords: Jatropha curcas L., pCAMBIA1301, plasmid DNA, stigma-drip